Efficient Multitask Scheduler for Heterogeneous Workloads with Varying Instruction Counts - Fadhil, Heba; Manickam, Selvakumar (Al-Khwarizmi Engineering Journal, 2025)
Multitasking systems need an efficient scheduling mechanism that minimizes the usage of resources and utilizes the system for improved output. This paper proposes an innovative scheduling framework that optimizes the distribution of resource allocation for tasks of different lengths that are run in shared computing environments. The integrated scheduler uses static and dynamic scheduling strategies for optimizing time performance and resource management. Static evaluation of the analytic process entails collection of task metrics, such as the frequency of instructions and the durations of runtime. The evaluation results demonstrate the formation of the initial scheduling framework. The frameworks perform execution dynamic optimizations that reorder priorities of execution whilst considering the growth of tasks with resource conditions. The proposed scheduler yields exceptional gains in execution efficiency and throughput of the system in experimental trials with many workloads relative to conventional practices. The airplane queue management powered by the scheduler ensures establishment of an optimal system, where workload is equally distributed amongst tasks without a conflict of resources to facilitate equal, timely completion. The proposed scheduler efficiently allocates load amongst tasks and hence decreases contention of resources and leads to fair execution. The proposed scheduler combines static and dynamic scheduling approaches to maximize the utilization of resources and to improve the performance of the system.